Do sustainable development policies in resource-based cities contribute to industrial structure upgrading? empirical evidence from China - Tong, Tong; Zhang, Tiegang (Frontiers in Environmental Science, 2025)
Sustainable development policies serve as the primary driver for the transformation and upgrading of resource-based cities (RBCs). This study analyzes how China’s Sustainable Development Plan of Resource-Based Cities, 2013-2020(SDPRC), which was implemented in 2013, affects the industrial structure upgrading in Chinese Resource-Based Cities. Taking SDPRC as a quasi-natural experiment, we assess this effect by using the panel data of prefecture-level cities from 2007 to 2023. The results of the study found that: (1) the coefficient of SDPRC on the RBC’s industrial structure upgrading is positive and passes the significance level test, indicating that SDPRC promotes the industrial structure upgrading of RBCs. (2) The SDPRC promotes the industrial structure upgrading of RBC through the green technology innovation effect, the human resource effect, and the FDI effect. (3) In the heterogeneity analysis, it is found that the promotion effect of SDPRC on the industrial structure upgrading of RBCs is significant in RBCs located at the southeast side of Hu Huanyong Line. The effect of policies on promoting industrial structure upgrading is also more pronounced in regions with higher per capita GDP. This paper enriches the empirical and theoretical support on how sustainable development policies facilitate the industrial structure upgrading of RBCs, while providing valuable insights for RBCs in other countries seeking transformative development.